PET Response-Guided Treatment of Hodgkin's Lymphoma: A Review of the Evidence and Active Clinical Trials - Paul Aridgides; Jeffrey Bogart; Anna Shapiro; Ajeet Gajra (Advances in Hematology)
Risk-adaptive therapy for Hodgkin's lymphoma focuses on treatment modifications based on assessment of response. [18F]Fluoro-deoxyglucose positron emission tomography (PET) performed during or after completion of chemotherapy is a strong prognostic factor for eventual treatment outcome. Conceptually, this strategy seeks to increase efficacy and minimize toxicity through the appropriate selection of patients for either therapy escalation (high-risk, PET positive) or de-escalation (low-risk, PET negative). Preliminary evidence with tailoring both chemotherapy (drug selection, number of cycles, and dose) and radiotherapy (omission or inclusion) is varied; however, numerous clinical trials seeking to validate this approach are ongoing. This paper summarizes the available evidence and active protocols involving PET response-adapted therapy for adult (early and advanced stages) Hodgkin's lymphoma.